The Influence of E-service Quality On Customer Satisfaction Mediated by E-trust (Empirical Study: Telemedicine Users at Hospital x Tangerang) - Edhi, Putu Kusuma; Heryjanto, Andreas (Journal of Management, 2024)
The number of patient visits to hospitals decreased as a result of the Covid 19 pandemic a few years ago. As a result, the hospital had to innovate to enable people, particularly those with certain conditions, to conveniently check their health without visiting the hospital. The digitization of telemedicine health services, which allow patients and physicians to have in-person consultations via communication technology like hospital video calls and conference calls, is one way that health services are innovating today in hospitals. The aim of this study is to ascertain the following: 1) how e-service quality affects customer satisfaction; 2) how e-service quality affects E-Trust; and 3) which E-Trust at RS X Tangerang mediates the effect of e-service quality on customer satisfaction. Through the use of questionnaires, outpatients at RS X Tangerang provided data for this descriptive quantitative study design. 120 patients made up the study's sample. The analysis's findings indicate that: (1) the E-service Quality (ES) variable influences the Customer satisfaction (CS) variable; (2) the E-service Quality (ES) variable greatly and favorably affects the E-Trust (ET) variable; and (3) the E-Trust (ET) variable greatly and favorably affects the Customer satisfaction (CS) variable.